Dilemmas of tolerance in contemporary art - Sztabiński, Grzegorz (Granice tolerancji w sztuce i w wychowaniu, 2020)
The author of the article distinguishes between „tolerance towards art” and „tolerance in art”. The former concerns the absence of individual or collective interference in creativity and the dissemination of its results. The latter refers to the renouncement of repression in the course of education, artistic activity and during the reception of performed works. While the acceptance of tolerance in the first sense can be taken for granted today, in the second case difficult choices emerge. One example is the twentieth-century avant-garde, which on the one hand fights for freedom for art and on the other – imposes various restrictions on art and its functioning. The contemporary artistic situation is characterized by democracy and pluralism. However, this is not free from dilemmas either. Some of them have been presented in more detail on the example of the concept of participatory art of Grant Kester, Nicolas Bourriaud and Claire Bishop. While the first two authors believe that the involvement of participants in artistic events should be based on dialogue and the creation of situations aimed at understanding, Bishop believes that the basis of true democracy is antagonism and therefore presupposes a clash of opposing views in art.